Sufism and Spiritual Education: The Role of Tasawwuf in Moral Development - Nissa Aurellia Putri; Samsul Arifin; Yola Mutia Damayanti; Ali Anhar Syi'bul Huda (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This article examines the role of Tasawwuf in spiritual education and its contribution to moral development within contemporary Muslim societies. Employing a normative and qualitative literature-based approach, the study analyzes scholarly works on Sufism, Islamic education, and moral formation to explore how Tasawwuf functions as an ethical and pedagogical framework. The findings reveal that Tasawwuf emphasizes inner spiritual purification, moral self-discipline, and the cultivation of virtues such as sincerity, compassion, and humility, which are essential for holistic moral development. Beyond individual character formation, Tasawwuf also strengthens collective ethics by fostering social responsibility, moderation, and moral resilience through communal spiritual practices and moral leadership. In educational settings, the integration of Tasawwuf contributes to value internalization by aligning spiritual consciousness with ethical behavior. The study concludes that Tasawwuf remains a relevant and adaptive moral resource capable of responding to modern social challenges, including digitalization and moral disorientation. Its integration into spiritual education provides a balanced approach that connects inner spirituality with ethical engagement in social life.